Information society and the workplace : spaces, boundaries and agency - Heiskanen, Tuula; Hearn, Jeff, 1947- (Routledge studies in technology, work and organizations, 2004)
Bringing together studies of everyday local practices in workplaces within information society, this book has a special focus on social space and the agency of actors. it includes both theoretical reviews and qualitative research.